Compliance Technology and Self-Enforcing Agreements - Bård Harstad; Francesco Lancia; Alessia Russo (Center for Economic Studies and ifo Institute (CESifo), 2015)
We analyze a repeated game in which countries are polluting as well as investing in technologies. While folk theorems point out that the first best can be sustained as a subgame-perfect equilibrium when the players are sufficiently patient, we derive the second best equilibrium when they are not. This equilibrium is distorted in that countries over-invest in technologies that are “green” (i.e., strategic substitutes for polluting) but under-invest in adaptation and “brown” technologies (i.e., strategic complements to polluting). It is in particular countries which are small or benefit little from cooperation that will be required to strategically invest in this way. With imperfect monitoring or uncertainty, such strategic investments reduce the need for a long, costly punishment phase and the probability that punishment will be triggered.
Keywords: D86; F53; H87; Q54; 330; climate change; environmental agreements; green technology; imperfect monitoring; policy instruments; repeated games; self-enforcing treaties